“It’s not easy to acknowledge that I’m ill”: a qualitative investigation into the health seeking behavior of rural Palestinian women - Majaj, Linda; Nassar, Majed; De Allegri, Manuela (BMC women's health, 2013)
This qualitative study sets to fill a gap in knowledge by exploring the health seeking behaviour of rural women living in the occupied Palestinian territories (oPt). The existing literature on the oPt has so far focused on unravelling the country’s epidemiological and health system profile, but has largely neglected the assessment of factors shaping people’s decisions on health care use.
Gesehen am 16.06.2021